A review of food additives to control the proliferation and transmission of pathogenic microorganisms with emphasis on applications to raw meat-based diets for companion animals - Kiprotich, Samuel S.; Aldrich, Charles G. (Frontiers in Veterinary Science, 2022)
Raw meat-based diets (RMBDs) or sometimes described as biologically appropriate raw food (BARFs) are gaining in popularity amongst dog and cat owners. These pet guardians prefer their animals to eat minimally processed and more “natural” foods instead of highly heat-processed diets manufactured with synthetic preservatives. The market for RMBDs for dogs and cats is estimated at $33 million in the United States. This figure is likely underestimated because some pet owners feed their animals raw diets prepared at home. Despite their increasing demand, RMBDs have been plagued with numerous recalls because of contamination from foodborne pathogens like Salmonella, E. coli or Campylobacter. Existing literature regarding mitigation strategies in RMBD’s for dogs/cats are very limited. Thus, a comprehensive search for published research was conducted regarding technologies used in meat and poultry processing and raw materials tangential to this trade (e.g., meats and poultry). In this review paper, we explored multiple non-thermal processes and GRAS approved food additives that can be used as potential antimicrobials alone or in combinations to assert multiple stressors that impede microbial growth, ultimately leading to pathogen inactivation through hurdle technology. This review focuses on use of high-pressure pasteurization, organic acidulants, essential oils, and bacteriophages as possible approaches to commercially pasteurize RMBDs effectively at a relatively low cost. A summary of the different ways these technologies have been used in the past to control foodborne pathogens in meat and poultry related products and how they can be applied successfully to impede growth of enteric pathogens in commercially produced raw diets for companion animals is provided.